Influence of pre- sowing treatment with eucalyptus and celandine on beet, wheat and corn seed sprouting - Y. P. Bondarev; T. A. Zubkova; Y. N. Ashinov; N. I. Mamsirov (Новые технологии, 2018)
Plant growth regulators are among the safest and show a stimulating effect on a wide range of plants. The scientific work is devoted to the study of the influence of pre-sowing treatment with eucalyptus (Folium Eucalypti) and celandine (Herba Chelidonii) on the development of wheat, beet and corn seedlings. Seed germination has increased by 2-12%. Eucalyptus showed the maximum effect on root growth: the root length increased by 3.7% for wheat, 15% for beets and 80% for corn in comparison with the control.